Critical distance in urban planning: will smart, sustainable and resilient narratives save our cities? insights from Delhi metropolitan area - Santos, S. (2019)
New Delhi is the second largest megacity in the world with a population of 26 million inhabitants (United Nations, 2016). Its metropolitan area its under severe vulnerabilities due to the lack of control of planning instruments on urban transformations. Needs in housing, resources (water and energy), infrastructures, transports, public services (health and education) among others are definitely going beyond local and regional government response capacities (Kapuria, 2014). Planning efforts, polices and regulations seem to have been instrumentalized under distinct historical moments, namely colonization, state control over land and nowadays capitalism and globalization. This leaded to the advent of an unplanned urbanism, with its extreme consequences and risks. It is intended to establish this nexus by revisiting the key planning moments in Delhi along with its different socioeconomic, cultural and political frameworks across time. Finally, we draw conclusions on how contemporary urban development models such as ‘sustainability’, ‘resilience’, ‘participated governance’ or ‘smart cities’ are being framed, perceived and applied under the context of Delhi urban planning instruments, polices and research. It seems that these narratives are serving as means to achieve specific goals by different drivers and actors. The discourse of sustainability is used to sell gated urbanizations for higher income classes, situated in greened areas, far way from slums and pollution. Resilience and horizontal governance is pursuit by the state as a mean to make citizens resistant and accountable to deal with city problems withdrawing public institutions from its own responsibility. Smart Cities Agenda is based on a huge investment on technologic information systems (Delhi is home to many ICT companies) on the hope to end mobility and pollution problems, leaving aside the fact that 77% of Delhi population live under poverty, in precarious housing or without infrastructure (sewage systems, water distribution and services) (Kushwaha, 2016). It is intended to highlight the importance of this reflection for a deep rethinking on concepts and practices in urban planning field, specially in what concerns its normative generalization without taking into account the influences and consequences of distinct political, social,